Tobacco advertisement exposure and tobacco consumption among youths in South America - Geneviéve Plamondon; Emmanuel Guindon; Guillermo Paraje (Instituto Nacional de Salud Pública, 2017)
Objective. To assesses the statistical association between exposure to tobacco marketing and tobacco consumption among adolescents in South America, by using data from the Global Youth Tobacco Survey. Materials and methods. Using data from the Global Youth Tobacco Survey (GYTS), the exposure to tobacco marketing at the school level was studied from advertising in TV, radio, massive public events and street advertisement. Tobacco behaviour was considered. The total pooled sample used was 134 073 youths from Argentina, Bolivia, Chile, Peru, Brazil, Uruguay, Suriname, Colombia, Guyana, Ecuador, Paraguay and Venezuela. Results. The exposure to tobacco marketing is positively and significantly associated to the probability of youths experimenting with tobacco (at least once in their lifetime). For regular smokers, exposure to tobacco marketing is positively and significantly associated to smoking intensity. Conclusions. These results call for the implementation of strong restrictions on tobacco advertisement of various types in South American countries.